(untitled) (The International Journal for Scientific Research, 2025)
This study explores the impact of technology-enhanced instruction, specifically video conversation practices, on the oral communication skills of first-year university students learning English as a Foreign Language (EFL). Over an 8-week period, a quasi-experimental mixed-methods design was implemented using the textbook Person to Person 1 as the core instructional material. Participants engaged in both traditional textbook activities and supplementary video-based conversation tasks. Data collection included pre- and post-speaking tests. Quantitative results from the speaking assessments revealed significant improvements in students’ oral fluency, pronunciation accuracy, and overall communicative confidence. The post-test scores demonstrated marked progress compared to the pre-test, indicating that the integration of video conversation tools contributed positively to language development. Qualitative feedback further supported these findings, with students reporting increased motivation, engagement, and a sense of autonomy in their learning process. The video-based practices enriched textbook-driven instruction by fostering interactive learning environments, enabling real-time feedback, and encouraging peer collaboration. These digital tools allowed learners to practice speaking in more authentic and dynamic contexts, bridging the gap between classroom exercises and real-world communication.The study highlights the pedagogical benefits of combining traditional language resources with modern communication technologies. It recommends that EFL curricula be updated to incorporate video conversation practices as a core component of oral skills development. Such integration not only enhances linguistic outcomes but also prepares students for the communicative demands of a digitally connected world.